Climate change and health distress - K. Solanki, Hariom; Singh, Manpreet; Paul, Sampriti (International Journal Of Community Medicine And Public Health, 2026)
Climate change represents a significant health threat to human populations, particularly affecting impoverished and low-income nations, making it a global health concern in the 21st century. An extensive literature search was performed from June to September 2025, utilizing databases like PubMed, Scopus, Web of Science, and Google Scholar. The search strategy included pertinent keywords and MeSH terms such as “climate change,” “global warming,” “health effects,” “non-communicable diseases,” “infectious diseases,” “mental health,” and “vulnerable populations,” combined with Boolean operators (AND, OR). This narrative review explores the various health impacts of climate change on different organ systems, including both direct and indirect effects and their consequences. Increased temperatures, extreme weather events, altered precipitation patterns, and heightened air pollution are linked to numerous health issues, such as cardiovascular diseases, neurological disorders, kidney ailments, and respiratory problems. The detrimental effects of heat stress, dehydration, and air pollution elevate the risk of heart attacks, arrhythmias, strokes, and neurodegenerative conditions. Prolonged exposure to air pollution is associated with cognitive decline, anxiety, and depression. Tackling these intricate challenges necessitates coordinated multisectoral efforts that focus on climate resilience, strengthening health systems, and implementing equity-centred adaptation strategies.